Methodological review of model-based cost-effectiveness analyses of school-based interventions to increase pupils’ level of physical activity (Journal of Physical Education (Maringá), 2019)
A large number of school-based interventions promoting physical activity have been developed. Due to difficulties of obtaining observational data on the long-term effect and cost consequences, modelling techniques offer opportunities to consider the long-term health and economic consequences. The aim of this is to provide an overview of modelling approaches applied in economic evaluations of school-based physical activity programmes. It identifies key methodological choices, challenges and areas with a lack of evidence.A literature search was conducted to identify all relevant studies published within the last 10 years. The included studies were described with focus on main methodological aspects, including the costs, effects and modelling techniques.  Results shows eight model-based economic analyses of school-based physical activity programmes were identified. The majority of these studies concluded that the interventions had a high probability of being cost-effective or even cost saving based on the national-specific thresholds. Although most studies did provide a description of the models, details on the methodological choices were not always transparent. Moreover, evidence on the effectiveness and inclusion of all relevant cost categories were found to be challenging. In concluion different modelling methodologies have been used to assess the cost-effectiveness of school-based physical activity programmes. Only few studies have evaluated the long-term cost-effectiveness and they have challenging methodological issues.